Dermoscopic evaluation of nail psoriasis: a cross-sectional study - Varma, Krishnendra; Kumar, Ujjwal; Jain, Praneeta (International Journal of Research in Dermatology, 2020)
Background: Psoriasis is a chronic inflammatory immune mediated disease that can involve skin, nails, scalp, etc. Nails can be involved in up to 90% of psoriatic patients in their lifetime. Also, psoriatic arthritis is commonly found in patients having nail involvement. Nail changes in psoriasis can be imperceptible to the unaided eye and easily missed on clinical examination. Onychoscopy has helped in improving diagnosing these subtle clinical features. Aim of the research was to study dermoscopic features in nails involved in psoriasis. Methods: 50 patients having clinically evident nail psoriasis, of which 2 were excluded due to positive KOH examination were recruited in the cross-sectional descriptive study. After clinical examination, all the nails were subjected to dermoscopic examination. The findings were tabulated in Excel and comparisons were made. Results: The common dermoscopic findings were pits (79.2%), splinter haemorrhage (72.9%), onycholysis (68.8%), subungual hyperkeratosis (50%), nail plate scales (50%), dilated PNF/LNF capillaries (20.8%), ridges (18.8%), leukonychia (14.5%), salmon spots (10.4%), fuzzy lunula (8.3%), and dilated hyponychial capillaries (6.3%). Conclusions: Dermoscopy is a simple, easy, rapid and an office-based technique. It helps in picking up subtle nail changes not visible to the naked eye. It also precludes from doing painful nail biopsy in nail disease without its skin manifestation. Onychoscopy helps in picking up early nail findings in psoriasis and thereby warning the patients against impending disease severity.